Factors Influencing Parental Acceptance of Trans Children and Young People: Findings from Trans Pathways. Issue 5 (6th October 2022) - Morgan, Helen; Heritage, Brody; Lin, Ashleigh; Perry, Yael; Cook, Angus; Winter, Sam; Watson, Vanessa; Wright Toussaint, Dani; O'Donovan, Amanda; Almeida, Renita; Strauss, Penelope
Abstract: Trans youth are at high risk of mental health difficulties and negative life events. Strong parental support is highly protective however there is little understanding of what factors facilitate the process of parental understanding and acceptance of a child's gender identity. We aimed to better understand a) preexisting factors influencing levels of parental acceptance of their child's gender identity; b) the factors parents find helpful in facilitating acceptance of their child's gender identity once they become aware; and c) how parents experience extended family, cultural and religious reactions. Using cross-sectional survey data, we explored the experiences of parents and guardians ( N = 194). Quantitative data were primarily analyzed using Bayesian regression models and qualitative data were thematically analyzed. Several factors were salient in influencing parental acceptance, including the nature of their child's gender identity, and levels of awareness and acceptance of the child's gender identity at time of initial parental awareness. Multiple factors aided acceptance, including information, peer support, and the quality of the dyadic relationship. Findings provide a better understanding of how parental acceptance of a child's gender identity develops. We provide recommendations on what may help parents to optimally support their child, such as accessible, good-quality information.